Spokane Paper - Modern Progress in Mining and Metallurgy in the Western United States - David W. Brunton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1910)
The list of our past-Presidents comprises the names of many who, in their official addresses, have sketched the current progress of the arts and professions with which they were familiar. Such addresses are, in my judgment, highly useful, setting forth the results of our own work as a society, and recalling to our minds the particular lines in which discussion would prove most fruitful. Following this course with some hesitation, I venture to offer an outline of the recent improvements and the present situation in mining and metallurgy in the Western United States. The wonderful advances in mechanics, chemistry, and electricity have all combined to aid these arts to such an extent that progress during the last decade has undeniably been more rapid than ever before in the history of the profession. In all mining countries improved transportation-facilities, in many instances called into existence by the traffic created by the mines themselves, have done much to enlarge the field of operations by the reduction of freight-, operating- and living-expenses, thereby bringing lower-grade properties into the producing class. Under normal conditions, as the age of a district increases, all these different factors should combine to off-set the augmented costs attendant on deep mining, and greatly tend to prolong the profitable life of the mines. The more recent and important improvements in our Western mining-practice which have contributed most towards the advancement of the art may be briefly summarized as follows; but, before beginning this portion of my address, I wish to thank most heartily the many engineering friends who have so